EduSynthAI : Synthesizing Knowledge through Intelligent AI Learning Assistance - Sunitha S; Sree Dhanya C; Rathi B (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The Course Learning Assistant is an AI-powered platform designed to streamline the discovery, browsing, and evaluation of educational courses. Tailored to enhance the learning experience, the platform offers personalized user interactions, AI-generated summaries, and intelligent course recommendations. It features secure user authentication, supporting various roles such as students, parents, teachers, and overall administrators (principals), each with role-specific access and functionality. The platform empowers students to browse courses by category, interact through comments and reviews, and benefit from AI-generated summaries and instant question-answering features. Parents can track student progress, assign quizzes, and manage performance, while teachers have control over course content, student management, and module updates with in their domain. The overall admin (principal) oversees platform-wide governance, ensuring seamless operations.